Reproductive performances of Black Bengal goat under semi-intensive and extensive conditions at rural areas in Bangladesh - Hasan, Md. Jahid; Ahmed, Jalal Uddin; Alam, Md. Mahmudul (Journal of Advanced Veterinary and Animal Research, 2014)
The current study was aimed to investigate the influence of housing system on female reproductive traits of Black Bengal goats at rural areas in Bangladesh during the period of July to December 2012. A total of 200 Black Bengal goats reared under semi-intensive (n=100) and extensive conditions (n=100) were selected considering their age, body weight, body shape, and conformation. In semi-intensive condition, average age at puberty was 197.82±12.58 days, and age at first conception was 292.96±0.50 days; whereas, these lengths were 208.82±12.60 days and 287.65±0.52 days in extensive condition, respectively. Age at first kidding was 448.26±25.48 days under semi-intensive condition, whereas under extensive condition it was 450.07±22.43 days. Under semi-intensive condition, average litter size at the first, second and third parity were 1.06±0.13, 1.76±0.12 and 1.96±0.12, respectively. In contrast, under extensive condition, these values were 1.01±0.10, 1.62±0.12 and 1.75±0.11, respectively. The average kidding interval under semi-intensive system was 190.2±20 days, and the length reduced to 178.23±0.50 days (p<0.01) in the case of extensive housing system. It is concluded that rearing under extensive condition provoked better reproductive performance in Black Bengal goats as compared to semi-intensive housing system at rural level in Bangladesh. http://dx.doi.org/10.5455/javar.2014.a37